1999
DOI: 10.1046/j.1365-313x.1999.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

A G‐box motif (GCCACGTGCC) tetramer confers high‐level constitutive expression in dicot and monocot plants

Abstract: Summary GUS reporter expression from 11 basal promoters (CaMV –90) with G‐box cores (CACGTG) was analysed to evaluate the regulatory roles of G‐box flanking sequences. While most G‐box motifs exhibited some tissue preference of gene expression, a distinct tissue‐specific expression was not apparent. However, one of 11 G‐box sequences, the G‐box 10 (GCCACGTGCC) tetramer, conferred a high‐level constitutive expression in seed, root, leaf, axillary bud, almost all parts of flower buds and pollen of transgenic tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 33 publications
0
85
0
Order By: Relevance
“…Plant G-box elements contain a CACGTG core sequence that is necessary for efficient binding of basic leucine zipper proteins, and sequences flanking the CACGTG core affect basic leucine zipper protein binding specificity (25) and gene expression in vivo (26). The G-box in the cucumisin promoter, a 10-bp perfect palindrome (5Ј-GACACGTGTC-3Ј), can be classified as a high affinity class I G-box element that binds type A G-box binding factor (GBF) (16).…”
Section: Discussionmentioning
confidence: 99%
“…Plant G-box elements contain a CACGTG core sequence that is necessary for efficient binding of basic leucine zipper proteins, and sequences flanking the CACGTG core affect basic leucine zipper protein binding specificity (25) and gene expression in vivo (26). The G-box in the cucumisin promoter, a 10-bp perfect palindrome (5Ј-GACACGTGTC-3Ј), can be classified as a high affinity class I G-box element that binds type A G-box binding factor (GBF) (16).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with a pG10-90:XVE..GUS transformant line, in which the ubiquitous G10-90 promoter (Ishige et al, 1999) drives inducible GUS expression, showed GUS expression that is highly dependent on 17-b-estradiol (Fig. 2, A and B).…”
Section: Stringency Of the Modified Inducible System In Transgenic Plmentioning
confidence: 99%
“…The XVE elements have been transferred into a single-site Gateway-compatible destination vector to allow highthroughput cloning of genes under the control of the inducible, ubiquitous promoter pG10-90 (Ishige et al, 1999;Curtis and Grossniklaus, 2003). Although useful, this vector does not allow easy cloning of other promoters to drive inducible expression.…”
mentioning
confidence: 99%
“…The chimeric activator gene cassette contains the EcR ligand-binding region transcriptionally fused to the 441-bp GAL4 DNA-binding domain (amino acids 1-147; Laughon and Gesteland, 1984), the 264-bp VP16 acidic activation domain (amino acids 413-490) from Herpes simplex virus (Dalrymple et al, 1985), and the D to F regions containing the ligand-binding domain (amino acids 206-539) of EcR from Choristoneura fumiferana (spruce budworm; Perera et al, 1999), introduced between the constitutive G10-90 promoter (P 10-90 ; Ishige et al, 1999) and the nopaline synthase terminator sequence (Nos 3#). In p1002, the VP16 domain is positioned N terminally followed by the GAL4 and EcR domains (VGE), whereas in p1003, the GAL4 domain is positioned N terminally followed by the VP16 and EcR domains (GVE; Fig.…”
Section: Plasmid Constructsmentioning
confidence: 99%